2010
DOI: 10.1186/1477-3155-8-15
|View full text |Cite
|
Sign up to set email alerts
|

PVP-coated silver nanoparticles block the transmission of cell-free and cell-associated HIV-1 in human cervical culture

Abstract: BackgroundPrevious in vitro studies have demonstrated that polyvinylpyrrolidone coated silver nanoparticles (PVP-coated AgNPs) have antiviral activity against HIV-1 at non-cytotoxic concentrations. These particles also demonstrate broad spectrum virucidal activity by preventing the interaction of HIV-1 gp120 and cellular CD4, thereby inhibiting fusion or entry of the virus into the host cell. In this study, we evaluated the antiviral activity of PVP-coated AgNPs as a potential topical vaginal microbicide to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
112
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(114 citation statements)
references
References 70 publications
1
112
0
1
Order By: Relevance
“…Notably, Lara et al demonstrated that a high concentration of polyvinyl pyrolidone-coated Ag-NPs (0.6 mg/mL) were only cytotoxic to a small population of cells, affecting the viability of 20% of the cells in the cervical explants. 30 In addition, our data show that Ag-NPs were stably bound to the polyurethane condom and were not significantly leached from the condom due to the interaction of the Ag-NPs with the nitrogen atom of the PUC. This feature could provide additional advantage for the product used at the mucosal surface since the Ag-NPs will be removed with the PUC after use.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Notably, Lara et al demonstrated that a high concentration of polyvinyl pyrolidone-coated Ag-NPs (0.6 mg/mL) were only cytotoxic to a small population of cells, affecting the viability of 20% of the cells in the cervical explants. 30 In addition, our data show that Ag-NPs were stably bound to the polyurethane condom and were not significantly leached from the condom due to the interaction of the Ag-NPs with the nitrogen atom of the PUC. This feature could provide additional advantage for the product used at the mucosal surface since the Ag-NPs will be removed with the PUC after use.…”
Section: Discussionmentioning
confidence: 68%
“…The same amounts of human cervical cancer cells (HeLa cells) were exposed to the Ag-NPs-coated PUC or noncoated PUC for different times (10,30, and 180 minutes). Then, the Ag-NPs-coated PUC or noncoated PUC was removed and the growth of HeLa cells was monitored at different days postexposure by using a cell proliferation (WST-1) assay.…”
Section: Toxicity Of Ag-nps-coated Pucmentioning
confidence: 99%
“…Hence, the silver-ZnO NC have acted upon the bacterial cell wall of E. coli, inhibiting its synthesis. According to Lara et al (2010a), bactericidal action based on the inhibition of cell wall synthesis could be another possible mechanism. This was further supported by the hypothesis that the bacteria following nano treatments become non-culturable due to inhibition of further cell division.…”
Section: Discussionmentioning
confidence: 99%
“…Nanoscale materials have emerged * Corresponding author. Email: a_b_das@hotmail.com as novel antimicrobial agents owing to their effectiveness in small doses, minimal toxicity and lack of side effects (Lara et al 2010(Lara et al , 2010a. Ag ions and Ag-based compounds are highly toxic to microorganisms, showing strong biocidal effects on as many as 12 species of bacteria including Escherichia coli (Zhao & Stevens 1998).…”
Section: Introductionmentioning
confidence: 99%
“…This is an important finding because the use of siRNA has been effective in treating ocular diseases 18 and nanoparticles have been determined to be safe for mucosal tissue delivery Moreover, the use of nanoparticles for microbicidal delivery to both the female reproductive tract and the rectal mucosa indicates the potential for this approach to target primary HIV-1 infection in mucosal tissues. 12,[50][51][52] The potential to knock down gene expression within the female reproductive tract and induce protection against a sexually transmitted disease could be developed not only for HIV-1, but also for other pathogens that utilize cell-specific receptors for infection. Thus, it is possible to engineer nanoparticles for the delivery of siRNA, either alone or in combination with anti-HIV drugs, to achieve protection against sexual HIV-1 infection.…”
Section: Articlementioning
confidence: 99%